The Regulation of Pedestrian Path on Corridor Jamin Ginting Street Berastagi District - Novrial, Novrial; Hamdani, Hamdani (Talenta Publisher, 2020)
Generally, the target of road corridor construction is to provide a quality pedestrian, give comfort to pedestrian as user of road corridor. In create a good regulation of pedestrian path, it is necessary full of rules and requirements as to improve comfort for user of road. The factors influence to physical comfort of pedestrian path are circulation, smell, bench, security and beauty. The location of this research is Jamin Ginting street between Monument Pahlawan with Monument Kol, Berastagi which it is often pass by tourist. However, the condition on pedestrian path at this region, there have not some requirements to create a good pedestrian path. The objective of research is to plan regulation of pedestrian path on JaminGintingstreetBerastagi, according to requirement to Iswanto and the Rule of Minister PU No. 03/PRT/M/2014 on pedestrian path. The method of research is descriptive research, and then it compares with requirements and rules after that the conclusion is Comfortable is included circulation, smell, bench, security and beauty on pedestrian path at Jamin Ginting street Berastagi do not have qualified according to Iswanto and rules Minister PU No. 03/PRT/M/2014 on a good pedestrian path. This research proposed a recommendation of design pedestrian path according to Iswanto and Rule Minister No 03/PRT/M/2014 on pedestrian path at Jamin Ginting street Berastagi.